Implementasi Akuntansi Lingkungan dan Size Terhadap Profitabilitas Usaha - Nunung Nurhayati; Verliani Dasmaran (Universitas Kristen Maranatha, 2022)
The purpose of this study is to examine environmental accounting and company size, the effect on stock returns, and the role of profitability in moderating environmental accounting and company size on stock returns on the IDX Kompas100 Index. The sample of this research is 27 Kompas100 index companies that have won the PROPER award between 2019 and 2021. The analysis in this study is a regression with one moderator variable (MRA). The results of the study prove that environmental accounting has an effect on stock returns. Firm size does not have a significant impact on stock returns. Profitability can moderate the effect of environmental accounting and size on stock returns.Keywords: Environmental Accounting, Size, Stock Return, Profitability